Climate smart agriculture: Mitigation and adaptation strategies at the global scale - Azadi, Hossein; Siamian, Narges; Burkart, Stefan; Moghaddam Movahhed, Saghi; Goli, Imaneh; Dogot, Thomas; Lebailly, Philippe; Teklemariam, Dereje; Astrida, Miceikiené; Passel, Steven van (Springer, 2022)
To address adaptation and mitigation strategies for climate change, researchers in the agricultural field have extended numerous technologies and practices known as climate-smart agriculture (CSA). The CSA has led to an important debate on sustainable development in the agriculture system and climate among the scientific and civil society. However, one of the main challenges is incorporating the effects of climate change into agricultural development planning. For effective adaptation, the set of technologies that the CSA concept comprises requires measures of policies to decrease vulnerability and improve the capacity of producers, especially smallholders. Therefore, the goal of this chapter is to expand and formalize the CSA conceptual framework by relying on the theory and concepts of global adaptation and mitigation strategies. Overall, the chapter provides some evidence of good practices and innovative strategies of upgrading the CSA approach to mitigation and adaptation strategies through development agencies and civil society, research and academia, etc.